2014
DOI: 10.1080/09658211.2014.910530
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for withdrawing belief in vivid autobiographical memories

Abstract: Previous studies have shown that many people hold personal memories for events that they no longer believe occurred. This study examines the reasons that people provide for choosing to reduce autobiographical belief in vividly recollected autobiographical memories. A body of non-believed memories provided by 374 individuals was reviewed to develop a qualitatively derived categorisation system. The final scheme consisted of 8 major categories (in descending order of mention): social feedback, event plausibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 76 publications
7
73
2
Order By: Relevance
“…Scoboria, Boucher, and Mazzoni (2015) found that the primary reason people retracted their belief in a memory was social feedback, such as someone telling you that your memory was not true. Our study found that people who were more compliant did not form more NBMs than people who were less compliant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scoboria, Boucher, and Mazzoni (2015) found that the primary reason people retracted their belief in a memory was social feedback, such as someone telling you that your memory was not true. Our study found that people who were more compliant did not form more NBMs than people who were less compliant.…”
Section: Discussionmentioning
confidence: 99%
“…Social feedback has been found to be one of the main contributors to fostering NBMs (Scoboria, Boucher, & Mazzoni, 2015) and hence we included the Gudjonsson Compliance Scale (Gudjonsson, 1989) in order to examine individual differences in social compliance.…”
Section: The Current Experimentsmentioning
confidence: 99%
“…Inspecting citations of the remaining studies then identified more recent work. This was not intended as an exhaustive search of every publication that mentioned retractors; rather it served to identify key published work that contained data that could be compared -at least on a conceptual or thematic level -to the findings of Wade et al (2014) and Scoboria et al (2015).…”
Section: Sources Of Datamentioning
confidence: 99%
“…Firstly, comparisons are made between the strategies that people have been shown to use to verify moderately significant events (e.g., Wade et al, 2014), and retractors' reports of coming to believe in or recollect traumatic memories of sexual abuse -is there any evidence that retractors use "high cost" reliable strategies to verify these life changing beliefs or recollections? Secondly, comparisons are drawn between retractors' accounts of the repudiation of their beliefs and recollections and the largest systematic exploration of this issue with naturalistic NBMs in the published literature to date (Scoboria, Boucher, & Mazzoni, 2015). Are the dynamics of withdrawing belief similar when the events are highly consequential?…”
mentioning
confidence: 99%
“…The most common reason is social feedback; that is, being told by another person that the remembered event did not happen or could not have happened (Scoboria, Boucher, & Mazzoni, 2015; see also Mazzoni et al, 2010). Other common reasons include reappraising the plausibility of the event, and discovering physical evidence to the contrary.…”
mentioning
confidence: 99%